Meningkatkan Literasi Keuangan Dengan Memperkenalkan Akuntansi Dasar Pada Siswa SMA Negeri 1 Demon Pagong - Maria Fatima B. Beribe; Maria Yohana Belang (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
The aim of community service (PKM) is to increase students' financial literacy through training and mentoring by providing Basic Accounting material. The material presented is the basic equation of accounting and financial reports. The form of presenting the material is conveying concepts and followed by practical work on solving case study questions. There is also additional material in the form of an introduction to Spreadsheets/Excel computers (accounting data). The material presented is a suggestion from the service partners considering that students do not fully understand this material in class learning and this material is important for participants, because according to data on accounting learning results for class XII IIS for the odd semester of the 2023/2024 academic year, it has only reached 87%. Participants are class XI students of SMA Negeri 1 Demon Pagong whose address is Jalan Pati Beda, Demon Pagong District, East Flores Regency. Methods for implementing activities include 1) Training, namely presenting material on basic accounting concepts and financial reports. 2) Mentoring, namely assisting participants in completing case study questions based on the concepts that have been presented. 3) Evaluation, namely using an instrument in the form of practice questions on preparing financial reports, then the results are analyzed using qualitative analysis to determine students' financial literacy related to participants' understanding of accounting learning, both in the basics of accounting and financial reports. The results show that the average score obtained by students in preparing financial reports is around 75-85. This indicates that students' understanding of the material and assistance regarding the basics of accounting to financial reports reached 80%. Participants who experience difficulties in preparing financial reports are due to incorrectly calculating the nominal amount in the account because there are too many numbers and the calculations are done manually, they easily forget accounts and their placement mechanisms, they have difficulty identifying the elements included in the financial reports and they lack interest in studying accounting.